Mechanical Stimulation Protects Against Chondrocyte Pyroptosis Through Irisin-Induced Suppression of PI3K/Akt/NF-κB Signal Pathway in Osteoarthritis - Jia, Shuangshuo; Yang, Yue; Bai, Yishu; Wei, Yingliang; Zhang, He; Tian, Yicheng; Liu, Jiabao; Bai, Lunhao (Frontiers in Cell and Developmental Biology, 2022)
Irisin, a myokine secreted by muscle during physical exercise, is known to have biological activities in different cell types. Chondrocyte inflammation and pyroptosis have been shown to play important roles in osteoarthritis (OA). In this study, we investigated the effects of exercise-induced irisin during different intensities of treadmill exercise in a rat OA model and the anti-inflammatory and antipyroptosis mechanism of irisin in OA chondrocytes. Forty-eight SD rats (n = 8) were randomly assigned to control (CG), OA (OAG), OA groups under different intensities of treadmill exercise (OAL, OAM, and OAH), OAM+irisin neutralizing antibodies group (OAM+irisin(NA)) . The levels of irisin and the severity of OA between groups were detected using ELISA, histology, immunohistochemistry, X-ray and computed tomography and magnetic resonance imaging. The anti-inflammatory and antipyroptosis mechanisms of irisin were investigated in vitro in OA chondrocytes preincubated with recombinant irisin (0, 5, or 10 ng/mL) for 1 h before treatment with interleukin-1β (IL-1β) for 24 h. mRNA and protein expression levels were determined using quantitative reverse transcription polymerase chain reaction, and western blot analyses. Morphological changes and cell death associated with pyroptosis were examined using transmission electron microscopy, flow cytometry and immunofluorescence. Moderate-intensity treadmill exercise increased the levels of irisin, exhibiting the best therapeutic effects on OA which could be suppressed by irisin neutralizing antibodies. Irisin not only recovered the expression of collagen II and attenuated that of MMP-13 and ADAMTS-5 in IL-1β-induced OA chondrocytes by inhibiting the PI3K/Akt/NF-κB signaling pathway, but also inhibited the activity of nod-like receptor protein-3 (NLRP3)/caspase-1, thus ameliorating pyroptosis in chondrocytes. In conclusion, moderate mechanical stimulation protects against chondrocyte pyroptosis through irisin-induced suppression of PI3K/Akt/NF-κB signal pathway in osteoarthritis.